Subprime Mortgage Crisis in the United States in 2007–2008: Causes and Consequences (part II) - Pajarskas, Vaidotas; Jočienė, Aldona (Ekonomika, 2015)
This is the second part of the qualitative and quantitative research on the subprime mortgage crisis in the United States in 2007–2008. The main purpose of this research is to determine the factors and how they contributed to the subprime mortgage crisis, what their causal links and effects on the markets and the whole economy were, and to assess what actions could have been taken by the Federal Reserve and the Government in order to mitigate or prevent the consequences of the subprime mortgage crisis and the housing bubble. In order to obtain the results, the authors performed a qualitative analysis of the scientific literature on the course of events and their development that led to the subprime mortgage crisis and focused on insufficiently regulated home mortgage market expansion, the impact on subprime mortgage crisis of financial innovations and financial engineering, poorly evaluated systemic risks and policy undertaken by both the U.S. Government and the Federal Reserve before and after the crisis. The quantitative research focused on two main parts: firstly, the analysis of dependencies between the causes of subprime mortgage crisis and the consequences using the statistical and regression analysis; secondly, an alternative path the Government and the Federal Reserve could have taken in their policy actions, and the results they could have produced have been explored. The authors believe that the results of the research could give useful guidelines to the central bankers and government officials on how to make long-term decisions that can help in preparing for the financial distress, mitigating the consequences when the crisis strikes, accelerating the recovery and even preventing the crisis in the future.
Keywords: banks; central bank; subprime mortgage crisis; mortgages